Comparison of Canine Forelimb Kinematic Joint Angles Collected with 2D and 3D Models - Sandberg, Gabriella S.; Torres, Bryan T.; Budsberg, Steven C. (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective The aim of this study was to compare a Joint Coordinate System (JCS) three-dimensional (3D) kinematic model of the canine forelimb with more widely used linear (LIN) and segmental (SEG) 2D models.Study Design It was an in vivo biomechanical study.Animals Normal adult mixed breed dogs were used in this study (n = 6).Methods Nineteen retroreflective markers were applied to the skin of dogs' right forelimbs. Dogs were trotted and walked through the calibrated testing space. The first five good trials were used to generate sagittal plane (flexion and extension angle) waveforms from 3 different models (JCS, LIN and SEG) for the shoulder, elbow and carpal joints. The JCS model also generated transverse and frontal plane joint angular data (internal/external and abduction/adduction angles) for all three joints. Minimum, maximum and total angular displacement was calculated for each joint. Comparison of sagittal plane waveforms was performed before and after waveform alignment using statistical parametric mapping.Results Each model produced similar sagittal plane waveforms, though the LIN model had a greater vertical shift along the y-axis for the shoulder and elbow. Before waveform alignment, differences were revealed between the LIN model when compared to JCS or SEG model at a trot. No differences were revealed at a walk. After waveform alignment, no differences were revealed between models at a walk or trot. There were no differences in angular displacement measurements between models before or after waveform alignment at a walk or trot.Conclusions The 3D JCS model reported in this study produced sagittal plane waveforms comparable to conventional 2D models while also providing joint specific information from other planes of motion.
Keywords: kinematics; gait analysis; canine forelimb; joint angles